Firing a Laser into the Sky Diverts Lightning Offering Greater Protection to Installations - Rathindra Nath Biswas (International Journal of Photochemistry and Photochemical Research, 2024)
Lightning bolts cause thousands of deaths every year worldwide. Since Benjamin Franklin’s invention of lightning rods made almost 300 years ago, the technology has not been changed even today. The same Franklin lightning rods are used on top of the buildings to steer lightning down to the ground so that they don’t pass through the buildings, and damage the structure or electrocute people. Researchers have recently developed a new type of lightning protection system called laser lightning rod (LLR) that uses powerful laser which is fired rapidly in the air during thunderstorms. An electrical current can flow via the plasma channel formed in the air by the strong laser beam. The channel of ionized air thus produced can be focussed on top of a conventional lightning rod installed at a secured location away from the vital installations to be protected, and extended to the thunderstorm cloud. The advantage is that the laser can steer lightning over a much wider area, because the virtual height of LLR is increased quite a bit. The LLR then deflects and directs lightning away from the vulnerable installations safely to ground through the conventional lightning rod located at a safe distance away from the installations to be protected. Moreover, the precision of the laser allows for real-time adjustments, ensuring optimal protection during varying storm conditions. The LLR system can be integrated with weather monitoring technology to predict and react to potential lightning strikes more effectively.
Keywords: Chirped pulse amplification. Multipass amplifier; Femtosecond; Filamentation; Laser; Pulse recompression